2015
DOI: 10.3892/or.2015.4408
|View full text |Cite
|
Sign up to set email alerts
|

MARCKSL1 exhibits anti-angiogenic effects through suppression of VEGFR-2-dependent Akt/PDK-1/mTOR phosphorylation

Abstract: Myristoylated alanine-rich C kinase substrate-like 1 (MARCKSL1) plays a pivotal role in the regulation of apoptosis and has been shown to maintain antitumor and metastasis-suppressive properties. In the present study, we examined the effects of MARCKSL1 as a novel anti-angiogenic agent on the inhibition of angiogenesis-mediated cell migration. MARCKSL1 also reduced vascular endothelial growth factor (VEGF)-induced human umbilical vein endothelial cell (HUVEC) proliferation, as well as capillary-like tubular st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…15D ). S100A4 , MARCKSL1 and BAG4 have been reported to play important roles in promoting tumour metastasis 39 40 41 42 43 44 45 46 47 48 . Thus, ELL(C595A) mutant might promote tumour metastasis through inducing these metastasis-associated genes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15D ). S100A4 , MARCKSL1 and BAG4 have been reported to play important roles in promoting tumour metastasis 39 40 41 42 43 44 45 46 47 48 . Thus, ELL(C595A) mutant might promote tumour metastasis through inducing these metastasis-associated genes.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, silencing of S100A4 via siRNA or shRNA and blocking of S100A4 via anti-S100A4 antibody can reduce metastasis formation by blocking stroma cell invasion 41 42 43 . MARCKSL1 exhibits anti-angiogenic effects through suppression of VEGFR-2-dependent Akt/PDK-1/mTOR phosphorylation 45 . BAG4 is a negative regulator of apoptosis, which also links to tumour aggressiveness and metastasis 47 48 .…”
Section: Discussionmentioning
confidence: 99%
“…It has a serious effect on the health and life of patients, is a burden to the family and society, and inflicts substantial social and economic costs (3). According to the data of one survey, it possesses the highest disability and mortality rate in China (4). The incidence rate is rising at an annual growth rate of 8.7%, reflecting China's aging population (1).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the defect in cell spreading, we also noted that MRP-KO cells migrated more slowly than WT cells. Although a number of studies have demonstrated both stimulatory and inhibitory roles for MRP in cell migration, in some cases dependent on site-specific MRP phosphorylation, the consensus is that, as we found, MRP depletion is associated with decreased migration (Chun et al, 2009;Finlayson and Freeman, 2009;Bjorkblom et al, 2012;Kim et al, 2016). Although the mechanism causing the decreased migration is unclear, delayed migration is also seen in FAK-KO cells, where it is also thought to be related to defective focal adhesion remodeling (Schober et al, 2007).…”
Section: Discussionmentioning
confidence: 55%